Penerapan Expressive Writing Therapy terhadap Penurunan Gejala pada Pasien Harga Diri Rendah dan Halusinasi - Erina Adriana Paramitha; Wita Oktaviana; Pudji Lestari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to determine the effectiveness of Expressive Writing Therapy in reducing symptoms in patients with low self-esteem and auditory hallucinations. This study used a quantitative method with a pre-experimental one-group pretest-posttest design. The results showed a significant increase in hallucination control scores (from 13.0 to 21.4; p=0.043) and self-esteem scores (from 13.0 to 22.2; p=0.042). In conclusion, expressive writing therapy is effective as a psychiatric nursing intervention to help patients recognize, control, and redirect responses to hallucinations and promote a more positive self-perception. Keywords: Auditory Hallucinations, Low Self-Esteem, Expressive Writing Therapy